DNA fingerprinting at farm level to map wheat variety adoption across Nepal. Issue 5 (29th July 2021) - Garapaty, Rijuta; Majumder, Rituparna; Thapa, Dhruba; Upadhyay, Shesh Raman; Baidya, Suraj; Basnet, Roshan; Bhandari, Deepak; Gade, Poornima; Paranjape, Vijay; Killian, Andrzej; Vijayaraghavan, Vijay Kannan; Acevedo, Maricelis
Abstract: Wheat is a staple crop in Nepal and is the third major cereal crop grown across the country. To improve productivity and increase the number of farmers growing wheat, the Nepal Agricultural Research Council (NARC), since 1962, has been releasing new wheat varieties with higher productivity and disease resistance. Accurate identification of the varieties grown in farmer's fields is critical for assessing the adoption levels and the impact of new varieties. This understanding can change the landscape of the wheat market and the overall vulnerability of the crop to diseases and abiotic stresses. Current methods of identification that rely on farmer description and morphological traits have been associated with ambiguity. The objective of this study was to determine the varietal adoption of wheat in the seven wheat‐growing provinces of Nepal using DNA fingerprinting technology. The study revealed that 'Gautam' and 'Vijay' are the most popular wheat varieties planted in the plain areas of Nepal. The area covered in these varieties during the 2018–2019 wheat season was 20.3 and 19.5% respectively. 'WK1204' was popular and mostly planted in the mountainous areas of Nepal during the October–May cropping season. The decommissioned varieties, including 'Lerma Roja‐64', 'Pitic62', 'Kalyansona', 'NL‐30', 'Siddhartha', 'Vaskar', 'Vinayak', 'Annapurna‐2', and 'NL 251' are still in use by 8% of wheat farmers across Nepal. Almost 38% of the varieties currently grown were released 20 yr ago. The varietal adoption was determined using molecular markers through fingerprinting, and its implications are discussed in this paper. Core Ideas: Accurate understanding of varietal adoption is critical for its dissemination and helps frame effective agricultural policies that benefit farmers and consumers. Accurate identification of the varieties in farmer fields is critical for assessing impact. DNA fingerprinting of wheat varieties is a reliable method to asses variety adoption.